CYCLODEXTRINS AND THEIR APPLICATION IN PHARMACEUTICAL INDUSTRY (REVIEW) - S. A. Kedik; A. V. Panov; V. S. Tyukova; M. S. Zolotareva (Разработка и регистрация лекарственных средств, 2019)
In the review describes the main properties of cyclodextrins and their potential use in the formulations in various dosage forms as excipients, by which it becomes possible to modify the solubility of drugs, increase the bioavailability and stability of the drug.